THE ROLE AND IMPORTANCE OF THE USE OF TACTICS IN FOOTBALL COMPETITIONS - Akhmedova, Fotima (Science technology&Digital finance, 2023)
Ways and importance of using tactics in football competitions. Selection of tactics and its importance depending on the opposing team in competitions. Rules in the use of tactics. What tactics are most used.